Global Transition to Renewable Energy - Pak, Alena; Vlčková, Jana; Jedlinský, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The aim of this thesis is to identify determinants that impact the global transition from fossil fuels to renewable energy systems. Firstly, an overview of global energy market and renewable energy markets is provided, including brief description of major renewable energy sources. Secondly, major determinants of transition to renewable energy are described based on the multi-level RE deployment path theory presented by the IEA/OECD. The factors include incentives for transition to renewable energy, market barriers and policy measures. Thirdly, a regression model analysis is used to test the factors identified, with the focus on the share of non-hydro renewable electricity in total electricity generation in OECD-34 and BRICS countries. Lastly, the results are used to propose the required improvements to facilitate global transition to sustainable energy systems.
Vedoucí práce: Jana Vlčková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses